A case study on pre-commissioning of power transformer / Mohd Harith Ahmad - Ahmad, Mohd Harith (2013)
After new power transformer has been set up on site and before it connect with power supply and loading the load, it is must to have to go through numbers of testing procedures for confirming the specifications and performances of a power transformer. The purpose of commissioning tests on transformer is to satisfy, to pre determined standards, that all the equipment erection is correct and that all the equipment connections or cables have been installed in accordance with the approved erection drawings and diagrams. This paper describes about some testing before commissioning of power transformer at site (Penang Port Sdn.Bhd., Pulau Pinang).